Purification of Wastewater of Ion Exchange Plant of Shiraz Petrochemical Complex in Iran using Reverse Osmosis Method - GHASEMIPANAH, KARIM; SYAVASH MADAENI, SAYED; TORABIAN, ALI (Asian Journal of Chemistry, 2010)
In present studies, the reverse osmosis (RO) is used for treatment of regeneration wastewater from ion exchange plant of Shiraz petrochemical complex, which at present the wastewater is discharged to evaporation lagoons without any treatment. Despite numerous research about using membrane processes for industrial wastewater treatment, there was no study about using reverse osmosis for treatment of wastewater form ion exchange regeneration process. So, considering the similarities between this kind of wastewater and brackish water or saline water, it has been hypothesized that reverse osmosis has the ability to remove dissolved solids from this kind of wastewater. Therefore, it is necessary to provide a pilot plant which has facilities for indicate and control of pressure, temperature and flux to evaluate and investigate the wastewater treatability. In this study, two variables, pressure and cross flow velocity have been chosen at three levels and each run of experiment continues for 5 h. Nine experiments have been done, to obtain the maximum flux and the minimum conductivity. Levels are 20, 25 and 30 bar for pressure and 0.27, 0.54 and 0.81 m/s for cross flow velocity. Results show that wastewater from ion exchange regeneration can be treated satisfactorily and during this study, conductivity has been decreased from 14400 μs/cm to about 558 μs/cm, under 30 bar pressure and 0.54 m/s cross flow velocity and the flux is 46.89 L/m2 h. Considering results of treated wastewater, the percentage of dissolved solid removal is almost higher than 95. This treated wastewater can be used for irrigation or other purposes.